Pre-Service Teacher’s Experience in Improving English Literacy of Through the Kampus Mengajar 7 Program - Anastasya, Santika; Rusli, Tri Indah; Nasrullah, Rahmat (Universitas Pahlawan Tuanku Tambusai, 2025)
The Kampus Mengajar Program is part of the Merdeka Belajar Kampus Merdeka (MBKM) policy which provides opportunities for prospective teacher students to be directly involved in improving the quality of education in elementary schools. This study aims to explore how pre-service teachers describe their experiences in overcoming challenges in improving students' literacy while participating in the Kampus Mengajar 7 program. This research uses a qualitative approach with a case study design, involving five students who have participated in the program. Data were obtained through semi-structured interviews and documentation. The results showed that students faced various challenges at school, such as low student interest in reading, limited learning media, and a shortage of English teachers. To address these challenges, students designed a needs-based literacy program that is fun and relevant, such as routine reading before lessons, reading corners, and the use of digital media such as Canva, Wordwall, and YouTube. Individual and group strategies were also implemented to make students more active and enthusiastic. Besides having an impact on improving students' literacy, involvement in this program also contributes to the development of students' pedagogical, social and technological competencies as prospective teachers. However, the sustainability of the program still depends on school support and teacher involvement. These findings show that the Kampus Mengajar not only has a positive impact on students, but also serves as a real learning platform for students in preparing themselves as professional educators in the future.